The Policy Implementation of the Local Regulations in the Special Region of Yogyakarta Number 1 of 2014 on Handling Homelessness and Beggars amid the Covid-19 Pandemic (Case Study of Yogyakarta CITY IN 2021) - sukmawati, Nurul; Darumurti, Awang (Universitas Muhammadiyah Yogyakarta, 2022)
The Homelessness and beggars are one of the social problems related to economic and educational factors in a particular society. This situation is not only motivated by physical and mental, but there is a large problem related to the state of powerlessness to meet basic needs, have health vulnerabilities, and the character of independence that erodes. The problem of homelessness and beggars also arises during the Coronavirus disease 2019 pandemic, In the city of Yogyakarta the problem of homelessness and beggars has been regulated of the local regulations in the special region of Yogyakarta number 1 of 2014 on handling homelessness and beggars to advance the welfare of the people of Yogyakarta City. The method used in this study is a qualitative method with descriptive research types, primary data from the results of interviewees and secondary data in the form of literature with data collection techniques to get accurate, clear and specific research. The results of this study are the handling cases of homelessness and beggars is a challenge for policy makers because the problems faced are so complex, The role of the government to deal with homeless and beggars in accordance with the local regulations in the special region of Yogyakarta number 1 of 2014 on handling homelessness and beggars amidst the covid-19 as its implementer is the department of social service of the Yogyakarta city that cooperates with the camp assessment to carry out preventive, coercive, rehabilitative, and social reintegration efforts to protect and empower homelessness and beggars.